2011
DOI: 10.1177/1403494811421825
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic status, labour market connection, and self-rated psychological health: The role of social capital and economic stress

Abstract: There were no differences in psychological health between non-manual employees in higher positions and other employed and self-employed SES groups among men or women. In contrast, the early retired, the unemployed and the category on long-term sick leave had significantly higher odds ratios of poor psychological health among both men and women throughout the multiple analyses. Both economic stress and trust affected this association (i.e., lowered the odds ratios of poor psychological health), but affected by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0
3

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 22 publications
(27 reference statements)
1
20
0
3
Order By: Relevance
“…First, different diagnostic criteria and instruments used to collect data have been reported to measure depression among working population, varying from a single question to various scales [Roberts and Lee, 1993;Stewart et al, 2003;Kessler et al, 2006;Gilmour and Patten, 2007;National Survey on Drug Use and Health, 2008;Hilton et al, 2009;da Silva-Junior et al, 2009;Santin et al, 2009;Lindstrom et al, 2012]. First, different diagnostic criteria and instruments used to collect data have been reported to measure depression among working population, varying from a single question to various scales [Roberts and Lee, 1993;Stewart et al, 2003;Kessler et al, 2006;Gilmour and Patten, 2007;National Survey on Drug Use and Health, 2008;Hilton et al, 2009;da Silva-Junior et al, 2009;Santin et al, 2009;Lindstrom et al, 2012].…”
Section: Discussionmentioning
confidence: 99%
“…First, different diagnostic criteria and instruments used to collect data have been reported to measure depression among working population, varying from a single question to various scales [Roberts and Lee, 1993;Stewart et al, 2003;Kessler et al, 2006;Gilmour and Patten, 2007;National Survey on Drug Use and Health, 2008;Hilton et al, 2009;da Silva-Junior et al, 2009;Santin et al, 2009;Lindstrom et al, 2012]. First, different diagnostic criteria and instruments used to collect data have been reported to measure depression among working population, varying from a single question to various scales [Roberts and Lee, 1993;Stewart et al, 2003;Kessler et al, 2006;Gilmour and Patten, 2007;National Survey on Drug Use and Health, 2008;Hilton et al, 2009;da Silva-Junior et al, 2009;Santin et al, 2009;Lindstrom et al, 2012].…”
Section: Discussionmentioning
confidence: 99%
“…For example, it has been measured as social support (i.e., support from family members and friends) [28], generalized trust (i.e., whether the individual felt that other people could generally be trusted) [23,28,33-36], trust in institutions and government (i.e., trust in public servants, government, local councils, large corporations) [34], reciprocity (i.e., whether the individual felt that other people were helpful most of the time) [23,28], social participation (i.e., membership in groups, organizations and voluntary associations) [23,28,29,35,37], neighbourhood cohesion (i.e., neighbourhood integration, connections and safety) [25,34], and voting in national elections [38]. The lack of consistency in the measurements of social capital is a well-known problem within the research field [39].…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence of poor self reported psychological health has increased over the last decades in surveys, reflected by an increase in the incidence of depression, anxiety and self-harm among young men and women in psychiatric hospital care statistics [16]. Poor psychological health has been shown to be associated with economic stress [17,18], ethnicity [17,18], socioeconomic status [17], emotional and instrumental support [18], trust [17-19] and alcohol risk consumption [20,21]. There are some earlier population-based studies on adults’ experiences of physical violence and mental health measured as self reported psychological distress [2,6,7,11-14,22-24].…”
Section: Introductionmentioning
confidence: 99%